2019
DOI: 10.1016/j.fuproc.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Membrane reactors for biodiesel production with strontium oxide as a heterogeneous catalyst

Abstract: A membrane reactor containing an immobilized heterogeneous catalyst is an alternative for traditional homogeneous-based catalyzed transesterification for biodiesel production. Major problems in homogeneous catalysis are related to catalyst recuperation and soap formation, which can be overcome by using heterogeneous catalysts. Conversion can be increased by a combination of reaction and separation, using membranes with a specific pore size. The aim of this work was to study the performance of different membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 31 publications
(45 reference statements)
0
13
0
Order By: Relevance
“… Torras and co-workers studied the immobilization of SrO catalysts on a membrane (in a catalytic membrane reactor). They reported that SrO was the strongest catalyst in conversion of sunflower oil into several types of methyl esters . Another traditional method for NP fabrication involves the thermal annealing of strontium carbonate (SrCO 3 ) prepared by mixing Sr­(NO 3 ) 2 and Na 2 CO 3 by heating to 900 °C under an inert atmosphere in a flow furnace.…”
Section: Methods Of Synthesis Of Sro Npsmentioning
confidence: 99%
See 1 more Smart Citation
“… Torras and co-workers studied the immobilization of SrO catalysts on a membrane (in a catalytic membrane reactor). They reported that SrO was the strongest catalyst in conversion of sunflower oil into several types of methyl esters . Another traditional method for NP fabrication involves the thermal annealing of strontium carbonate (SrCO 3 ) prepared by mixing Sr­(NO 3 ) 2 and Na 2 CO 3 by heating to 900 °C under an inert atmosphere in a flow furnace.…”
Section: Methods Of Synthesis Of Sro Npsmentioning
confidence: 99%
“…The configuration comprising the physical immobilization of the catalyst over the membrane reached a methyl ester yield of >90 wt %. 108…”
Section: Porous Support Materials For Sro Npsmentioning
confidence: 99%
“…The permeate stream is comprised of biodiesel, methanol, glycerol and catalysts (Baroutian et al 2010;Dubé et al 2007). Hapońska et al (2019) investigated membrane reactors ( Fig. 1a) for biodiesel production using strontium oxide as a heterogeneous catalyst.…”
Section: Membrane Reactors For Biofuel Productionmentioning
confidence: 99%
“…A filled SrO non-woven bag was placed on the surface of a commercial polysulfone (PSF) membrane supplied by GE Osmonic to catalyze the transesterification of sunflower oil by Haponśka et al 99 According to Figure 23, the reaction products were pumped from the top layer at a rate of 400 mL/ h, then filtered, and returned to the recycling container. The commercial membrane used in this study significantly enhanced the contact between the reactants, the membrane surface, and the catalyst.…”
Section: Biodiesel By Membrane-separation-enhanced Transesterificationmentioning
confidence: 99%
“…Equipment used for transesterification: (a) CMR and (b) IMRCF. This figure was reproduced with permission from ref . Copyright 2019 Elsevier.…”
Section: Biodiesel By Membrane-separation-enhanced Transesterificationmentioning
confidence: 99%